Dog population dynamics in a rabies free area of Malaysia (Serdang) - Wan Nur Shaqeena Wan Abdul Razak. (2019)
Although rabies has not been eliminated from Malaysia, it has been declared free over the years until 2012 when outbreaks occurred from 2015 until today. Establishing a quantitative data on canine population dynamics in Malaysia would not only enhance rabies control but would also unveil its transmission dynamics. This study report observations on canine population density and the basic reproductive value (R₀) in a supposedly rabies free area devoid of an immune belt, i.e Seri Serdang. A survey of population density and R₀ of owned dogs free roaming dogs in Serdang was carried out via client record survey and photographic mark recapture (PMR) method over a 3 weeks period. The PMR was done at 0630 to 1000 and 1600 to 1830 for four consecutive days. It is found that the dog population density of 1.55 dog/km² for owned and free roaming while the R₀ for rabies was 0.49 and 0.99 (range 0 – 3). These preliminary findings can provide support for the feasibility of controlling canine rabies in this area by vaccination of both the owned and free roaming dogs